Bramble and Maggie spooky season - Haas, Jessie; Friend, Alison (Somerville, Massachusetts Candlewick Press, 2016)
"In Bramble and Maggie's third adventure, a new season is here--fall! Leaves crunch underfoot. Acorns ping off rooftops. But when Halloween comes, can Maggie trust her horse to brave the tricks and lead them both safely to the treats?"--
"Ages 5-9"
Keywords: Autumn -- Fiction; Halloween -- Fiction; Horses -- Fiction